Hemostatic challenges in patients with chronic immune thrombocytopenia treated with eltrombopag. (February 2014) - Tarantino, Michael D.; Bakshi, Kalpana K.; Brainsky, Andrés
<x xml:space="preserve">Abstract</x> Chronic immune thrombocytopenia (ITP) is an autoimmune disease that results in chronically low platelet counts. Treatment guidelines recommend a platelet count of at least 50 000/µl before minor surgery and at least 80 000/µl before major surgery. This retrospective analysis explored invasive non-dental procedures associated with the risk of bleeding (hemostatic challenges) among patients with chronic ITP in five phase 2/phase 3 studies of the thrombopoietin-receptor agonist, eltrombopag. Data collection for patients who underwent hemostatic challenges included demographics, study medication, timing of the procedure, platelet counts at last assessment before and first assessment after the procedure, supplemental ITP treatment, and bleeding events. Among 494 patients who participated in the studies, 87 hemostatic challenges were recorded. Median platelet counts before 44 major procedures in 32 patients were 100 000/µl and 18 500/µl among patients who received eltrombopag and placebo, respectively; before 43 minor procedures in 38 patients, median platelet counts were 82 000/µl and 20 000/µl among patients who received eltrombopag and placebo, respectively. A minority of patients required supplemental ITP treatment. Only 2 of 87 hemostatic challenges were associated with bleeding events; both patients received eltrombopag and pre-procedural platelet counts were 83 000/µl and 2000/µl. Although the number of patients who did not undergo procedures due to thrombocytopenia was not captured, these data suggest a majority of patients with chronic ITP who receive eltrombopag and experience increases in platelet counts meet current pre-procedural platelet count recommendations. The potential role of eltrombopag in supporting preparation of chronic ITP patients for surgical procedures still needs to be clinically established.